2017
DOI: 10.1002/ceat.201700138
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Palm Fatty Acid Distillate Using a Sulfonated Mesoporous CuO‐ZnO Mixed Metal Oxide Catalyst

Abstract: A nanocrystalline mesoporous CuO‐ZnO hollow sphere was successfully fabricated by the hydrothermal method. The nanocomposite was formed in the presence of polyethylene glycol as a dispersant and D‐glucose as a template. The mesoporous CuO‐ZnO catalyst was further functionalized with benzenesulfonic acid to catalyze the esterification of palm fatty acid distillate (PFAD). The physicochemical, textural, structural, and thermal properties of the mesoporous CuO‐ZnO mixed‐oxide catalysts were evaluated. The modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…114 The synthesized mesoporous SO 3 H-ZnAl 2 O 4 catalyst was further utilized for methyl ester production, where the synthesized catalyst was able to stay highly active for eight continuous esterication reaction cycles without needing further recovery. 115 The CHNS results revealed that the sulfur content leaching was insignicant from the rst to the eighth cycle (dropped from 2.23 to 1.50 wt%). The remarkable stability of the synthesized mesoporous SO 3 H-ZnAl 2 O 4 catalyst corresponded to the polymeric attachment of SO 3 H groups to the inner pore walls under proper post-sulfonation conditions.…”
Section: Post-synthetic Functionalization Approachesmentioning
confidence: 98%
See 1 more Smart Citation
“…114 The synthesized mesoporous SO 3 H-ZnAl 2 O 4 catalyst was further utilized for methyl ester production, where the synthesized catalyst was able to stay highly active for eight continuous esterication reaction cycles without needing further recovery. 115 The CHNS results revealed that the sulfur content leaching was insignicant from the rst to the eighth cycle (dropped from 2.23 to 1.50 wt%). The remarkable stability of the synthesized mesoporous SO 3 H-ZnAl 2 O 4 catalyst corresponded to the polymeric attachment of SO 3 H groups to the inner pore walls under proper post-sulfonation conditions.…”
Section: Post-synthetic Functionalization Approachesmentioning
confidence: 98%
“…Similarly, nanocrystalline mesoporous mixed metal oxide (carbon@CuO-ZnO) spheres were hydrothermally fabricated. 89 The effects of different Cu : Zn ratios (0.5, 0.75, and 1.0) on the textural properties were examined; upon raising the metal ratio, the surface area was enhanced (419.13, 477.54, and 517.03 m 2 g À1 ) while the pore size decreased (3.35, 3.11, and 2.88 nm). In another research work, polymeric mesoporous mixed metal oxides (ZnAl 2 O 4 ) with different Al/(Zn + Al) molar ratios (0.5, 0.75, and 1.0) were hydrothermally synthesized.…”
Section: Non-silica Based Mesoporous Materialsmentioning
confidence: 99%
“…According to the results, N 2 adsorption did not come into view at a low pressure (P/P o < 0.5), indicating a weak adsorption of N 2 for the mesostructured samples. On the other hand, N 2 adsorption/desorption overlapped as a hysteresis loop at P/P o > 0.5, which implied mesopore formation [21][22][23]. It is noteworthy that the monolith does not contribute to the S BET , and the reported values only represent the S BET for the deposited carbon on the monolith.…”
Section: Textural Properties Of the Adsorbentmentioning
confidence: 95%
“…The superior reusability of the SO 3 H-NiO-ICG catalyst was associated largely with the S BET of the catalyst where larger pore size gives better opportunity to sulfonic functional species to incorporate into the mesopore frameworks. [37][38][39] Generally speaking, ANN as an effective quantiable procedure was highly suitable for modelling the selected operative input variables (such as metal ratio, surfactant and template concentrations, and calcination temperature) to predict the mean of surface area values of the synthesized mesoporous SO 3 H-NiO-ICG catalyst. Furthermore, introducing ANN examination as an efficient numerical model would largely save the budget and time by foreseeing the outputs of the analytical procedure.…”
Section: Methyl Ester Productionmentioning
confidence: 99%